PENINGKATAN PRESTASI BELAJAR IPA MELALUI PEMANFAATAN BARANG BEKAS SEBAGAI SUMBER BELAJAR - Lusia Endang Rahayuningsih (Jurnal Penelitian Pendidikan, 2015)
This study aims to determine whether the use of second-hand goods as a source of learning can improve students’ learning results. This research is a qualitative research using action research approach in school. The main data obtained from informants such as school principals, and teachers. Data were collected by observation, interview and documentation methods. The results showed that the scientific utilization of thrift as a source of learning can improve student achievement. It was shown by: (1) Increasing activity of student learning qualitatively that was shown by an increase in the average value of students’ learning activities from the initial data 18.03 into 21.50 in the first cycle and increased to 25.30 in the second cycle. Learning activities of students are in the active category. In quantitative, students who are active in science learning increase from the initial data that only 40% to 63.335% in the first cycle and increased to 90% in the second cycle or from 12 students to 19 students in the first cycle and moving up to 27 students in second cycle ; (2) Improvement of student learning outcomes demonstrated by average value increase of the initial data 69.19 to 74.67 in the first cycle and 83.17 on the second cycle as well as an increase in the students percentage of mastery learning of the initial data 46, 67% increase to 66.67% in the first cycle and became 93.33% in the second cycle.